Increase in viability, production of reactive oxygen species, IL-1 and TNF-α in human peripheral blood mononuclear cells treated with fucoidan from Lessonia trabeculata - Colona‐Vallejos, Erasmo H. (2019)
Brown algae are a source of high content of polysaccharides such as fucoidans that have important immunomodulatory properties. The aim was to determine the viability of human peripheral blood mononuclear cells (hPBMC), production of nitric oxide (NO), reactive oxygen species (ROS) and the proinflammatory cytokines IL-1α, IL-6, TNF-α and IFN -γ in cultures treated with fucoidan from Lessonia trabeculata. Fucoidan from Lessonia trabeculata from San Nicolás de Marcona-Ica Bay was used. The hPBMC were isolated using Ficoll-Hypaque, distributed at a concentration of 1x105 cells/well in complete RPMI-1640 medium and treated with different concentrations of fucoidan for 24 and 48 h. The cytotoxic activity was determined by the reduction of MTT, NO production by the Griess reaction and ROS by the reduction of NBT. The production of cytokines was quantified by ELISA. The fucoidan of L. trabeculata stimulated the proliferation of hPBMC and produced the increase of ROS at concentrations of 100-2000 μg/mL with respect to the control (p <0.001), the reaction for nitrites was negative. Fucoidan increased the production of IL-1α and TNF-α at concentrations of 100 and 10 μg/mL respectively, while the production of IL-6 and IFN-γ did not show significant differences. It is concluded that the fucoidan of L. trabeculata stimulates the proliferation of hPBMC, production of reactive oxygen species and the proinflammatory cytokines IL-1α and TNF-α that possess important immunomodulatory properties.